Interactive Storytelling with Hand Puppets for Improving Speaking Skills in Children with Speech Delay - Wahyuni, Wahyuni; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Speech delay affects 3-20% of early childhood populations globally, impacting communication abilities, social interaction, and academic readiness. Hand puppet storytelling represents a potentially effective intervention approach combining narrative engagement with interactive visual elements to stimulate verbal responses in affected children. This classroom action research employed the Kemmis and McTaggart model across two intervention cycles. One 5-year-old participant with identified speech delay received hand puppet storytelling sessions twice weekly over six weeks. Data collection utilized structured observation checklists assessing seven speaking skill indicators, semi-structured teacher interviews, and anecdotal records. Quantitative analysis calculated percentage improvements, while qualitative data underwent thematic analysis. Significant speaking skill improvements were demonstrated from baseline assessment (28.57%) to post-intervention (62.5%), representing a 33.93% increase that exceeded the predetermined 30% success criterion. Five out of seven assessment indicators achieved "Developing Appropriately" status. Progressive enhancement occurred across verbal responsiveness, vocabulary usage, sentence construction, speaking confidence, and storytelling participation. Qualitative findings revealed increased spontaneous verbal initiation, enhanced peer interactions, and improved classroom confidence. The intervention's effectiveness aligns with previous research supporting narrative-based language interventions and puppet-mediated therapeutic approaches. Results demonstrate that classroom teachers can successfully implement evidence-based speaking skill interventions without specialized therapeutic training, providing cost-effective alternatives to traditional speech therapy methods. The study addresses existing research gaps by documenting practical implementation within regular educational settings rather than controlled experimental conditions.